HIV-DNA Given with or without Intradermal Electroporation Is Safe and Highly Immunogenic in Healthy Swedish HIV-1 DNA/MVA Vaccinees: A Phase I Randomized Trial. - Charlotta Nilsson; Bo Hejdeman; Karina Godoy-Ramirez; Teghesti Tecleab; Gabriella Scarlatti; Andreas Bråve; Patricia L Earl; Richard R Stout; Merlin L Robb; Robin J Shattock; Gunnel Biberfeld; Eric Sandström; et al. (PLoS ONE, 2015)
We compared safety and immunogenicity of intradermal (ID) vaccination with and without electroporation (EP) in a phase I randomized placebo-controlled trial of an HIV-DNA prime HIV-MVA boost vaccine in healthy Swedish volunteers.HIV-DNA plasmids encoding HIV-1 genes gp160 subtypes A, B and C; Rev B; Gag A and B and RTmut B were given ID at weeks 0, 6 and 12 in a dose of 0.6 mg. Twenty-five volunteers received vaccine using a needle-free device (ZetaJet) with (n=16) or without (n=9) ID EP (Dermavax). Five volunteers were placebo recipients. Boosting with recombinant MVA-CMDR expressing HIV-1 Env, Gag, Pol of CRF01_AE (HIV-MVA) or placebo was performed at weeks 24 and 40. Nine of the vaccinees received a subtype C CN54 gp140 protein boost together with HIV-MVA.The ID/EP delivery was very well tolerated. After three HIV-DNA immunizations, no statistically significant difference was seen in the IFN-γ ELISpot response rate to Gag between HIV-DNA ID/EP recipients (5/15, 33%) and HIV-DNA ID recipients (1/7, 14%, p=0.6158). The first HIV-MVA or HIV-MVA+gp140 vaccination increased the IFN-γ ELISpot response rate to 18/19 (95%). CD4+ and/or CD8+ T cell responses to Gag or Env were demonstrable in 94% of vaccinees. A balanced CD4+ and CD8+ T cell response was noted, with 78% and 71% responders, respectively. IFN-γ and IL-2 dominated the CD4+ T cell response to Gag and Env. The CD8+ response to Gag was broader with expression of IFN-γ, IL-2, MIP-1β and/or CD107. No differences were seen between DNA vaccine groups. Binding antibodies were induced after the second HIV-MVA+/-gp140 in 93% of vaccinees to subtype C Env, with the highest titers among EP/gp140 recipients.Intradermal electroporation of HIV-DNA was well tolerated. Strong cell- and antibody-mediated immune responses were elicited by the HIV-DNA prime and HIV-MVA boosting regimen, with or without intradermal electroporation use.International Standard Randomised Controlled Trial Number (ISRCTN) 60284968.